Actitud ante la responsabilidad ética en estudiantes del posgrado de medicina, UNMSM, 2021 - Izaguirre Sotomayor, Manuel (2022)
Introduction: Ethical responsibility obliges the health professional to seek excellence, to prevent negligence or crime, keeping professional skills up to date, which allow him to evaluate what is good or bad, what he can or cannot do, to provide quality, safe care based on scientific and ethical evidence. Objective: to determine the attitude towards ethical responsibility of postgraduate students of the Faculty of Medicine, UNMSM. Materials and Methods: Non-experimental design, comparative cross-sectional descriptive method of quantitative approach. Instrument: Likert Scale Questionnaire validated in content by expert judgment and reliability with pilot test and Cronbach's Alpha coefficient (0.941). Sample made up of 316 postgraduate students (second specialty, master's degrees, doctorates). Data analysis: It was carried out by applying the analysis of non-inferential descriptive statistics, for each one of the dimensions. Results: The general average of the negative attitude towards ethical responsibility was 25.50%, with the highest negative score corresponding to the dimension of professional practice (41.50%) and decision-making (36.10%). The indifferent attitude was higher in women than in men in the dimensions of medical care, decision-making, moral commitment and professional practice. Conclusion, in the sample studied, the attitude towards ethical responsibility was positive in 74.42%, and indifferent in 25.5%, that is, there is an ethical commitment of professionals to comply with everything that corresponds to them in their professional practice.